The Problem of Alleviating the Poor in the Special Autonomy Governance of Aceh Province - Pribadi, Muhammad Akbar; Regif, Surya Yudha (Ministry of Home Affairs, 2022)
The issuance of Law of the Republic of Indonesia Number 18 of 2001 concerning Special Autonomy for the Province of the Special Region of Aceh as the Province of Nanggroe Aceh Darussalam and Law Number 11 of 2006 concerning the Government of Aceh are the efforts of the central government to improve the welfare of the people in Aceh Province. During the 20 years of the special autonomy, it has not played a significant role in alleviating the people’s poverty in Aceh. The dynamics of local politics, culture, and history, as well as the lack of organizational and managerial capacity at the sub-national and national levels, are suspected as the culprits of the failure of decentralization. The research objective is built on a perspective that refers to three specific aspects, namely the Governance Dynamics Perspective, the Governance Strategy Perspective, and the Governance Capacity Perspective, to analyze the governance of special autonomy in Aceh Province in alleviating the Poor. Through the literature study method, we will dig up a lot of accurate information and data related to the Alleviation of the Poor in the Special Autonomy Governance of Aceh Province. The research results found that the special autonomy going on so far was the designation of political agreements aimed at regional elites, not the general public. Local government administration's ineffective control is also influenced by the exogenous relationship between governance and regional development in alleviating poverty. In summary, the regional government of Aceh Province does not yet understand: (1) the need for supervision involving the community, (2) the absence of a monitoring mechanism so that the community is not affected, (3) local government effectiveness, (4) lack of information facilities, (5) coordination of public apparatus, (6) inefficient and ineffective service delivery, (7) lack of institutional capacity, (8) human resources, (9) the complexity of the central-regional relationship, (10) local elite power struggle, (11) in the Aceh Special Autonomy Law, regional leaders and local political parties have no responsibility or role in improving welfare. This causes (1) the imbalance between the income of the poor and the expenditure on primary and secondary needs, (2) the poor in Aceh cannot meet a decent standard of living due to low skills based on the size of the poverty line, (3) the quality and competence of human resources due to education cause low public participation in public policies, (4) high transaction costs due to limited access, low connectivity between regions, and limited supply of goods, production facilities, and infrastructure, (5) strategically fluctuating basic commodity prices and low regional government control.